Neofunctionalization of Duplicated Genes Under the Pressure of Gene Conversion - Teshima, Kosuke M. (Genetics Society of America, 2008)
Neofunctionalization occurs when a neofunctionalized allele is fixed in one of duplicated genes. This is a simple fixation process if duplicated genes accumulate mutations independently. However, the process is very complicated when duplicated genes undergo concerted evolution by gene conversion. Our simulations demonstrate that the process could be described with three distinct stages. First, a newly arisen neofunctionalized allele increases in frequency by selection, but gene conversion prevents its complete fixation. These two factors (selection and gene conversion) that work in opposite directions create an equilibrium, and the time during which the frequency of the neofunctionalized allele drifts around the equilibrium value is called the temporal equilibrium stage. During this temporal equilibrium stage, it is possible that gene conversion is inactivated by mutations, which allow the complete fixation of the neofunctionalized allele. And then, permanent neofunctionalization is achieved. This article develops basic population genetics theories on the process to permanent neofunctionalization under the pressure of gene conversion. We obtain the probability and time that the frequency of a newly arisen neofunctionalized allele reaches the equilibrium value. It is also found that during the temporal equilibrium stage, selection exhibits strong signature in the divergence in the DNA sequences between the duplicated genes. The spatial distribution of the divergence likely has a peak around the site targeted by selection. We provide an analytical expression of the pattern of divergence and apply it to the human red- and green-opsin genes. The theoretical prediction well fits the data when we assume that selection is operating for the two amino acid differences in exon 5, which are believed to account for the major part of the functional difference between the red and green opsins.